Lessons from the Contraceptive CHOICE Project: the Hull long-acting reversible contraception (LARC) initiative. Issue 1 (18th September 2014) - Trussell, James; Guthrie, Kate
Abstract : Aim: To discover whether a hand-out explaining the benefits of intrauterine contraceptives (IUCs) and implants could increase their uptake in Hull, UK. Methods: We developed a simple double-sided A4 hand-out. On one side was a script with pictures of copper and levonorgestrel IUCs next to a 20 pence coin and of an implant beside a hairgrip. On the other side was the three-tiered effectiveness chart published in the textbook Contraceptive Technology . We implemented the project in family planning (FP), abortion and antenatal clinics and general practitioner (GP) surgeries. The plan was that the receptionist would give the hand-out to every woman and ask her to read it before seeing a clinician. We evaluated the hand-out in FP clinics and GP practices because routine electronic monitoring reports were available only for these locations. Results: There was no impact in GP practices. There was no overall impact in FP clinics, with the exception of the service hub, in which there was an increase in the proportion of women receiving IUCs or implants of 15.0% between the periods October 2011–April 2012 and May 2012–November 2012 ( p =0.0002). This clinic is open 6 days per week and has permanent sexual health staff on the reception desk. The proportion of women receiving IUCs or implants returned to baseline in December 2012–November 2013, when a change in clinic procedure to reduce waiting times caused staff to stop dispensing hand-outs. Conclusions: This was not a formal study, so there was no research coordinator to monitor the project. We think that there was no impact among GPs because the project was not implemented by them. The project was poorly implemented at the four satellite FP clinics. Only the service hub implemented the project, where it had a clear impact. We conclude that when implemented as intended, this simple, very low-cost long-acting reversible contraception intervention was highly effective and also extremely cost effective.